2020
DOI: 10.1097/mao.0000000000002938
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Vestibular Schwannoma Enlargement After Radiosurgery Using Tumor Shape and MRI Texture Features

Abstract: Objective: Determine if vestibular schwannoma (VS) shape and MRI texture features predict significant enlargement after stereotactic radiosurgery (SRS). Study Design: Retrospective case review. Setting: Tertiary referral center. Patients: Fifty-three patients were selected who underwent SRS and had a contrast-enhanced T1 sequence planning MRI scan and a follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Recently, radiomics‐based methods combined with traditional machine learning techniques have been applied to different prediction tasks for VS 14,15,31–33 . Although promising prediction performance was achieved for post‐radiosurgery response/enlargement prediction and active treatment requirement prediction, none of these methods provides end‐to‐end prediction, because tumor delineation is a prerequisite for MRI radiomics feature extraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, radiomics‐based methods combined with traditional machine learning techniques have been applied to different prediction tasks for VS 14,15,31–33 . Although promising prediction performance was achieved for post‐radiosurgery response/enlargement prediction and active treatment requirement prediction, none of these methods provides end‐to‐end prediction, because tumor delineation is a prerequisite for MRI radiomics feature extraction.…”
Section: Discussionmentioning
confidence: 99%
“…Different from tumor enlargement detection which is based on tumor size measurement on follow‐up images, tumor enlargement prediction (TEP) methods predict the probability of significant tumor volume growth in the early stage of VS diagnosis. Recent works have shown that VS MRI radiomic feature analysis with machine learning methods is predictive for TEP, which has the potential to be used as a basis for individualized treatment planning 14–16 . However, these studies focus on TEP for post‐radiosurgery VS only, and 3D delineation of VS is needed as a prerequisite for radiomic feature extraction.…”
Section: Introductionmentioning
confidence: 99%
“…The recent literature consists of AI applied to otological imaging in a range of modalities and clinical contexts (Table 1). Groups have combined AI with computed tomography (CT) [4–14], magnetic resonance imaging (MRI) [15–17,18 ▪ ,19,20] and light otoscopy/otoendoscopy [21 ▪ ,22,23,24 ▪▪ ,25,26,27 ▪ ,28–31,32 ▪▪ ]. Most of the recent literature focuses on two themes: automated, image-based otoscopic diagnosis and automated segmentation of temporal bone CT and MRI scans for use in virtual reality, surgical simulation and surgical planning.…”
Section: Artificial Intelligence and Otological Imagingmentioning
confidence: 99%
“…George-Jones trained a support vector machine (SVM) algorithm to use tumour shape and texture information from MRI scans of vestibular schwannomas (VS) to predict a greater than 20% volumetric growth 6 months post radiosurgery with a sensitivity of 92% and specificity of 65% [15]. Langhuizen's SVM model examined a longer follow up period of 129 months post VS radiosurgery and demonstrated 83% sensitivity and 82% specificity [17].…”
Section: Artificial Intelligence and Predicting Vestibular Schwannoma...mentioning
confidence: 99%
“…In the context of VS, previous work has shown that a cystic or heterogenous appearance on MRI was associated with an increase in Antoni type B/mixed tissue 7 . In addition, recent studies have established relationships between MRI texture parameters and the prediction of VS enlargement after radiosurgery 8–10 . Although these results are promising and exciting, the aforementioned texture analysis studies in VS all take place in the context of tumors that did not undergo surgical resection, and therefore, there has been no correlation between these texture parameters and underling tumor histology.…”
Section: Introductionmentioning
confidence: 99%